x-(4+3x)=16

Simple and best practice solution for x-(4+3x)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(4+3x)=16 equation:


Simplifying
x + -1(4 + 3x) = 16
x + (4 * -1 + 3x * -1) = 16
x + (-4 + -3x) = 16

Reorder the terms:
-4 + x + -3x = 16

Combine like terms: x + -3x = -2x
-4 + -2x = 16

Solving
-4 + -2x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -2x = 16 + 4

Combine like terms: -4 + 4 = 0
0 + -2x = 16 + 4
-2x = 16 + 4

Combine like terms: 16 + 4 = 20
-2x = 20

Divide each side by '-2'.
x = -10

Simplifying
x = -10

See similar equations:

| p+6.5=-1.2 | | (x+2)/6=2/5 | | 3x^2+12=12x | | -8=x/4+1/2 | | 10y=4y+8+5y | | 2p-9p=6p+7 | | 7x=11x+8 | | 4z-2z-x+3z+2x=18 | | -12(n+6)-n=-2(2-2n) | | -4c+2=-50 | | 3(x-5)+1=2(x+1)-7 | | 0.15x+0.40(150)=0.35(x+150) | | 5x^2+17-12=0 | | 2y-2y+5y-4y=18 | | -15=5(1-2) | | 100=-4u | | 8x+9=90 | | 6x+5=5+4x+14 | | -2(x+8)=2(1-3x)+6x | | 5=-4(4)-11 | | 16a+3a-10a-2a=7 | | 2-6=-5(x+4)-39 | | -3(2-2+8)=-12 | | 25-3x=3 | | 11d-d-7d+2d-3d=12 | | -5+7a+3=33 | | y+(5+3)=32 | | (3x-4)(3x-8)=35 | | 6*m^2+m^2= | | 3(8+2a)=12-2a | | -12(n+12)=-12-12(10+n) | | 10q-5q=15 |

Equations solver categories